PENGUJIAN BERBAGAI FORMULASI PUPUK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN MELON (Cucumis melo L) PADA LAHAN KERING MASAM - Adi Oksifa Rahma Harti; Ina Ilmayanti; Acep Atma Wijaya (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2021)
Melon (Cucumis melo L.) contains various important vitamins and minerals, while melon consumption in Indonesia is still far below the standard. The increase in melon production every year has not met the needs of melons. Intensification of acid dry land is one of the efforts to increase melon production, because of the vast potential of the land, but it is necessary to improve the soil properties. The purpose of this study was to test the formulations on the growth and yield of melon plants on acid dry land. The study was conducted in a greenhouse using a non-factorial Randomized Block Design (RBD), with 8 treatments, namely: (A) without Lime + Phonska NPK Fertilizer (100%); (B) without Lime + Phonska NPK Fertilizer + Cow Manure (50%:100%); (C) without Lime + Phonska Npk Fertilizer + Petrobio Fertilizer (50%:100%); (D) without Lime + Phonska NPK Fertilizer + Cattle Fertilizer + Petrobio Fertilizer (50%:50%:50%); (E) with Lime + Phonska NPK Fertilizer (100%); (F) with Lime + Phonska Npk Fertilizer + Cow Manure (50%:100%); (G) with Lime + Phonska Npk Fertilizer + Petrobio Fertilizer (50%:100%); (H) with Lime + Phonska Npk Fertilizer + Cow Manure + Petrobio Fertilizer (50%:50%:50%) with 4 replications. Data analysis used Duncan's Multiple Range Test. The results showed that the fertilizer formulation with additional lime had a significant effect on fruit weight, fruit diameter, and fruit harvest age. Fertilization formulation without the need for high doses of organic fertilizer to achieve optimal yields.